Dissemination and implementation of the Cooking with Kids tasting curriculum - Diker, Ann, author; Cunningham-Sabo, Leslie Derry, advisor; Anderson, Jennifer, advisor; Baker, Susan S., committee member; Kaminski, Karen, committee member; Most, David E., committee member (Colorado State University. Libraries, 2010)
Numerous school health education programs, including nutrition education curricula have been developed. To improve dissemination and implementation of nutrition education curricula in schools, research is needed to identify and measure factors that facilitate and hinder the dissemination and implementation processes. Therefore, this study was conducted to identify strategies and practices that aided dissemination, adoption, and implementation of the Cooking with Kids (CWK) tasting curriculum by paraprofessional Nutrition Educators (NE). The study used a mixed methods time-series design. Formative assessment data were collected from two web-based surveys (n=313) and 27 interviews. The assessment results and constructs of Diffusion of Innovations and Social Cognitive Theory were used to develop a three-hour training introducing CWK to NE and their supervisors. Intervention data were collected from paraprofessional NE (n=49) and their supervisors (n=21) using a series of surveys, interviews, and implementation reports. Quantitative data analysis included descriptive analysis, factor analysis, analysis of variance, paired samples t-tests, correlations, and multiple regression. Qualitative data were analyzed for themes. Formative assessment revealed active participation, lesson observation, and pilot-testing as essential features of effective paraprofessional NE training. From pre- to post-training, NE and supervisors reported improved knowledge about teaching the curriculum (t=5.12, p<0.01 and t=8.31, p<0.01, respectively), confidence (t=3.93, p<0.01 and t=3.62, p<0.01, respectively), motivation (t=3.71, p<0.01 and t=2.63, p<0.05, respectively), and information (t=7.17, p<0.01 and t=4.15, p<0.01, respectively) to teach the curriculum. Gains in NE knowledge, confidence, motivation, and communication skills were sustained eight months post-training. Gains in supervisor knowledge were sustained eight months post-training. Supervisor motivation to use CWK returned to pre-training levels, which were relatively high to begin with so there was limited room for improvement. Although supervisor confidence was higher at eight months post-training, it was not statistically different from pre-training levels. These results may be attributed to the fact that supervisors did not teach the tasting lessons. High levels of curriculum adoption and implementation by NE were attributed to strong implementation expectations, experiential and observational learning training elements, and perceived curriculum compatibility with existing programming. Environmental factors such as time constraints, personnel turnover and scheduling conflicts proved challenging. Study results underscore the importance of combining theory and formative assessment for successful development and implementation of training and, in turn, curriculum implementation. In addition, results indicate that perceived simplicity, compatibility, and trialability are important attributes that should be maximized when introducing new curricula to potential adopters.
Keywords: Nutrition -- Curricula -- Development; Children -- Nutrition -- Study and teaching (Elementary); Nutrition -- Study and teaching (Elementary); Food -- Sensory evaluation -- Study and teaching (Elementary)